REMOTE SENSING IN PHYTOSOCIOLOGY: THE MAP OF VEGETATION OF THE PROVINCIA OF ROME - FANELLI, F.; BIANCO, M.P.; D'ANGELI, D.; DE SANCTIS, M.; SERAFINI SAULI, A.; TESTI, A.; PIGNATTI, S. (Annali di Botanica, 2005)